The International Encyclopedia of Media Psychology 2020
DOI: 10.1002/9781119011071.iemp0168
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mediation of Media Use and Effects

Abstract: Parental mediation refers to parents' efforts to monitor and regulate children's and adolescents' media use, as well as their comments and discussion about media content with their children. Mediation has nearly always assumed a purpose of preventing negative media effects. However, definitions of the concept have evolved as new media technologies have given children increasingly private and mobile access to media content. Within the family, a complex array of parent‐ and child‐related demographic, social, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…The differences and similarities in parental mediation amongst countries are, furthermore, at least partly based on parents’ online experiences and technological opportunities, which in turn are related to national wealth (Helsper et al, 2013; Talves & Kalmus, 2015). Moreover, parents adapt their mediation strategies to their perceptions of children's needs and online experiences (Warren, 2020). As a generalisation, we may say that the degree of the mediatisation of family as a socialising environment, evidenced by the intensity of children's and parents’ internet use, influences parental mediation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences and similarities in parental mediation amongst countries are, furthermore, at least partly based on parents’ online experiences and technological opportunities, which in turn are related to national wealth (Helsper et al, 2013; Talves & Kalmus, 2015). Moreover, parents adapt their mediation strategies to their perceptions of children's needs and online experiences (Warren, 2020). As a generalisation, we may say that the degree of the mediatisation of family as a socialising environment, evidenced by the intensity of children's and parents’ internet use, influences parental mediation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These arguments may explain why parents’ and children's reports on parental mediation do not always line up. Parents report higher levels of mediation than do their children for all media platforms (Vaterlaus et al, 2014; Warren, 2020). For example, in a study comparing the reports from parents and children on parental mediation of children's video game playing, Nikken and Jansz (2006) found that parents and children systematically differed from each other in their perceptions of different types of mediation: parents claimed to mediate more than the children did, and the differences were largest for restrictive and active mediation.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on parental mediation (Warren, 2020) suggests a rather linear trajectory-mediation reduced as children move toward adulthood. Several theories of relational communication, however, encourage the examination of mediation as a process by which parents and children manage the uncertainty of relational and role transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that parents’ levels of mediation are associated with characteristics of both the parents and children (Warren, 2020). Higher levels of mediation were identified among more educated parents, higher income parents, and parents who worked fewer hours outside of the home.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation